TRANSPORTASI LAUT KONTAINER DALAM PENGEMBANGAN MASTER PLAN PERCEPATAN DAN PERLUASAN EKONOMI INDONESIA DI INDONESIA BAGIAN TIMUR - Langas Denny Siahaan; Shirly Wunas; M. Yamin Jinca; Muh. Saleh Pallu (Forum Studi Transportasi antar Perguruan Tinggi (FSTPT), 2013)
Potential demand of sea transport for containers will grow rapidly along with the development of the processing industry in the region development of the integrated economic and regional strategies or Economic Corridor in the Master Plan of the Accelaration and Expansion of Indoneisa Economic Development in Eastern Indonesia. There were changes in the function of the port into a multipurpose port serving conventional and container freight. The problem that arises is the pier and container handling facility requires adjustment unless neither special container port Makassar and Bitung, nor the limited land development for land side facilities. Geometric conditions of the road connecting the port to the hinterland and have not planned for container services. Collector and feeder ports require adjustments to the revitalization of demand load wheels and multi-pack.